2015
DOI: 10.1017/s1366728915000784
|View full text |Cite
|
Sign up to set email alerts
|

Re-assembling objects: a new look at the L2 acquisition of pronominal clitics

Abstract: Cambridge University PressEditorial Office of BLC: 1 (804) 289-8125 F o r P e e r R e v i e w• L1 feature combinations influenced initial L2 mapping (Feature Reassembly H.);• L2 learners successfully reassembled features into L2 bundles (off-line task);• L1 representations might have a longer-lasting impact on language processing;• L2 learners' reactions to the mismatching input delayed compared to natives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 72 publications
0
7
0
4
Order By: Relevance
“…This is relevant because, as mentioned in the introduction, English differs from both Spanish and French in terms of encoding the [±Human] feature, since the pronominal system does encode [±Human] (e.g., he/she vs. it). Previous research with Anglophone learners of French revealed differences in reading time patterns depending on the value of the [±Human] feature (Shimanskaya and Slabakova 2017). Thus, we cannot rule out that the L2 learner group could be influenced by the other languages in their repertory.…”
Section: Discussionmentioning
confidence: 80%
“…This is relevant because, as mentioned in the introduction, English differs from both Spanish and French in terms of encoding the [±Human] feature, since the pronominal system does encode [±Human] (e.g., he/she vs. it). Previous research with Anglophone learners of French revealed differences in reading time patterns depending on the value of the [±Human] feature (Shimanskaya and Slabakova 2017). Thus, we cannot rule out that the L2 learner group could be influenced by the other languages in their repertory.…”
Section: Discussionmentioning
confidence: 80%
“…In terms of the L2 speakers, we expected their behaviour to be less clear cut but, most importantly, modulated by the L1 properties. First and foremost, we anticipated there to be a distinct asymmetry between offline (i.e., judgment) and online (i.e., eye movement) data, in light of previous research (cf., Papadopoulou and Clahsen 2003;Marinis et al 2005;Shimanskaya and Slabakova 2017;Stepanov et al 2019). Although we have argued that online knowledge may be modulated by underlying linguistic knowledge, it is likely that delayed lexical access and/or limited computational resources may prevent learners from applying this knowledge during real-time processing.…”
Section: Research Questions and Predictionsmentioning
confidence: 99%
“…The results may be accounted for by L1 transfer effects as well as a task effect and the use of explicit learning strategies. Using insights from Lardiere (2004Lardiere ( , 2008Lardiere ( , 2009 and Hawkins et al's (2006) concerning feature reassembly and feature expression on the English articles, as well as insights from Cho and Slabakova (2014), Shimanskaya and Slabakova (2014), and Slabakova's (2009bSlabakova's ( , 2009cSlabakova's ( , 2016 concerning notions of covert vs. overt and direct vs. indirect form-meaning expressions of functional morphemes, we argue that the article use patterns exhibited by the intermediate L2 English learners were due to L1 transfer and its interaction with the L2 input data.…”
Section: Cjl/rclmentioning
confidence: 99%
“…Other scholars have reasoned that variability in English article acquisition patterns among L2 learners (L2 speakers) stems from mismatches in feature specifications on the lexical items between the learners' L1 and the target L2, and thus requires feature reassembly for successful acquisition (Hawkins et al 2006;Lardiere 2004Lardiere , 2005Lardiere , 2008Shimanskaya 2015;Shimanskaya and Slabakova 2014). Other factors are whether the functional morphemes are overtly expressed in both the L1 and L2, whether they are overt in the L1 and covert in the L2, or whether they are overt in the L2 and covert in the L1 (Cho and Slabakova 2014;Slabakova 2009aSlabakova , 2009bSlabakova , 2016.…”
Section: Introductionmentioning
confidence: 99%